Risk of Metachronous Advanced Neoplastic Lesions in Patients with Sporadic Sessile Serrated Adenomas Undergoing Colonoscopic Surveillance. (June 2016) - Pereyra, Lisandro; Zamora, Rafael; Gómez, Estanislao Jesús; Fischer, Carolina; Panigadi, Guillermo Nicolas; González, Raquel; Bun, Maximiliano; Mella, José Manuel; Omodeo, Mariana; Luna, Pablo; Amante, Marcelo; Casas, Gabriel; et al.
Abstract : OBJECTIVES: The risk of developing metachronous advanced neoplastic lesions (ANLs) during surveillance after resection of sessile serrated adenomas (SSAs) has not been quantified. METHODS: Patients with sporadic SSAs resected between 1 April 2007 and 31 December 2009 who underwent surveillance colonoscopy in our institution were prospectively evaluated. Patients with low‐risk adenomas (LRAs), high‐risk adenomas (HRAs), and negative index colonoscopy (NIC) during the same period were identified using the pathology database and electronic medical records, and were also included as a comparison cohort. The primary outcome was the comparison of the study groups with regard to incidence of metachronous ANLs during surveillance colonoscopy. RESULTS: A total of 185 patients had SSAs, of whom 75 with 101 resected polyps were finally included. The comparison cohort consisted of 564 patients: 140 LRAs (160 polyps), 87 HRAs (478 polyps), and 337 NICs. The overall mean colonoscopy follow‐up was for 54.5 months (±s.d. 14). SSA patients with synchronous HRA on index colonoscopy presented a higher incidence rate of metachronous ANL (12.96 per 1, 000 person‐months) compared with patients with HRA (5.07 per 1, 000 person‐months), whereas those with synchronous LRA and without synchronous adenoma on index colonoscopy presented a low incidence rate of metachronous ANL (0 and 1.41 per 1, 000 person‐months, respectively) similar to LRA (1.47 per 1, 000 person‐months). Among patients with SSA the 3‐ and 5‐year ANL free‐cumulative probability was 64.3 and 32.1% in those with synchronous HRA, 100 and 100% in those with synchronous LRA, and 95.1 and 91.7% if no synchronous adenoma was found. CONCLUSIONS: Among patients with resected sporadic SSAs the risk of developing metachronous ANL is influenced by the presence of synchronous HRA on index colonoscopy. Patients with SSAs and synchronous HRA on index colonoscopy require closer surveillance, whereas those with synchronous LRA and those without synchronous adenomas may be followed up in the same way as those with LRAs.